The Russian Revolution - Sheila Fitzpatrick (UOxford niversity Press, 2001)
This provocative and eminently readable work looks at the many upheavals of the Russian Revolution as successive stages in a single process. Focusing on the Russian Revolution in its widest sense, Fitzpatrick covers not only the events of 1917 and what preceded them, but the nature of the social transformation brought about by the Bolsheviks after they took power. Making use of a huge amount of previously secret information in Soviet archives and unpublished memoirs, this detailed chronology recounts each monumental event from the February and October Revolutions of 1917 and the Civil War of 1918-1920, through the New Economic Policy of 1921 and the 1929 First Five-Year Plan, to Stalin's "revolution from above" at the end of the 1920s and the Great Purge of the late 1930s